Apremilast in psoriasis – a prospective real‐world study. (12th October 2017) - Vujic, I.; Herman, R.; Sanlorenzo, M.; Posch, C.; Monshi, B.; Rappersberger, K.; Richter, L.
Abstract: Background: Apremilast is a novel oral phosphodiesterase‐4 inhibitor approved for psoriasis treatment. Randomized trials have documented its efficacy and safety, but data on real‐world patients are scarce. Objectives: We aim to characterize psoriasis patients treated with apremilast in a real‐world setting and calculate drug survival as an important measure of efficacy and compliance. Methods: All patients with psoriasis who received apremilast between 1 April 2015 and 19 January 2017 were evaluated every 4 weeks, and we documented: age, weight, height, smoking status, family history of psoriasis, joint involvement, previous treatments, psoriasis area severity index (PASI) scores, and the onset and duration of adverse events (AE). Efficacy was analysed by PASI50, PASI75 and PASI90, reflecting the improvement of skin lesions compared to the PASI‐baseline. Kaplan–Meier statistics were used for drug survival estimates. Results: Forty‐eight patients were included. The median apremilast drug survival was 12.5 weeks (range 1–87). Three patients (6.3%) reached PASI90, nine (18.8%) PASI75 and eight patients (16.7%) PASI50. Patient weight inversely correlated with a PASI50 response ( P < 0.05, n = 37), and none of the obese patients (BMI > 30.0, n = 6) reached PASI75, compared to 32% of the non‐obese patients (BMI < 30.0, n = 31). Thirty‐one patients (64.6%) reported at least one AE, most frequently diarrhoea ( n = 21, 43.8%), headache ( n = 7, 14.6%) and joint pain ( n = 5, 10.4%). Conclusions: Despite differences between real‐world and trial patients, apremilast is safe and effective for the treatment of skin psoriasis in the daily practice. Up to 40% of patients will reach PASI50 or higher, but only few patients will reach PASI90. Bodyweight might affect drug efficacy.